Meningkatkan Literasi Digital Melalui Pelatihan Aplikasi Kinemaster Untuk Pembuatan Konten Pembelajaran - Gamar Al Haddar; Akhmad Ramli; Baso Intang Sappaile; Retno Dewi Prisusanti; Hilya Wildana Sofia (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2023)
This service activity is intended to explore the potential use of technology to improve digital literacy among students by utilizing the Kinemaster application as an innovative learning tool. Digital literacy is a crucial factor in individual success in a society that relies on information technology, and multimedia applications such as Kinemaster are considered to have a significant role in achieving this goal. The approach applied in this PKM is to provide training to participants, especially students and teachers, on the use of Kinemaster applications to create multimedia content that supports learning. They are taught how to edit videos, add multimedia elements, and produce interesting learning materials through this application. The positive impact of this activity involves improving participants' digital literacy skills, increasing their ability to use technology for learning, and increasing their interest in creative exploration through multimedia. The positive contribution of this PKM is reflected in the development of digital literacy among students, supporting a more interactive and technology-based learning process, and creating opportunities for participants to become more skilled and responsible multimedia content producers.